Some Fixed Point Theorems for Generalized \(α\)-\(η\)-\(ψ\)-Geraghty Contractive Type Mappings in Partial \(b\)-Metric Spaces (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we introduce the notion of generalized \(α\)-\(η\)-\(ψ\)-Geraghty contractive type mappings in the set up of partial \(b\)-metric spaces and \(α\)-orbital attractive mappings with respect to \(η\). Furthermore, the fixed point theorems for such mappings in complete partial \(b\)-metric spaces are proven without assuming the subadditivity of \(ψ\). Some examples are also provided for supporting of our main results.
Keywords: Generalized \(α\)-\(η\)-\(ψ\)-Geraghty contractive type mappings; \(α\)-orbital attractive mappings with respect to \(η\); Complete partial \(b\)-metric spaces; Fixed points